Pelatihan Kiat-Kiat Cara Mengelola Keuangan - Martcelina, Tri Salma; Marlinah, Aan; Wijaya, Novia; Prajitno, Sugiarto (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2024)
Training on financial management is an important need in the digital era, especially in facing the challenges of online loans (pinjol) that are increasingly prevalent. This research aims to improve financial literacy through financial management training for teachers at Yayasan Petra Alpha School Jakarta, with a focus on understanding the risks of online lending and how to manage personal finances wisely. The method used was interactive lectures, where the material was delivered with explanations on the importance of financial planning, budgeting, saving, investing, and distinguishing between needs and wants. The results of the training showed that most participants began to understand the importance of good financial management to achieve financial stability, although some participants still had difficulty in recording income and expenses systematically. The training also equipped participants with practical skills in managing debt and utilizing technology to monitor expenses. Evaluation of the training showed that with a better understanding of financial management, teachers can make wiser financial decisions and avoid financial problems due to reliance on online loans.